2015
DOI: 10.5688/ajpe79564
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Achievement Goal Orientations and Academic Performance Among Students at a UK Pharmacy School

Abstract: Objective. To ascertain goal orientations of pharmacy students and establish whether associations exist between academic performance, gender, or year of study. Methods. Goal orientations were assessed using a validated questionnaire. Respondents were categorized as high or low performers based on university grades. Associations and statistical significance were ascertained using parametric and nonparametric tests and linear regression, as appropriate. Results. A response rate of 60.7% was obtained. High perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 27 publications
1
23
1
1
Order By: Relevance
“…Prior limited work in health professions education suggests associations between achievement goals (measured with various instruments) and academic performance, self-efficacy, burnout and frustration. [29][30][31][62][63][64][65][66] However, validity evidence for achievement goals assessments in the health professions has been sparsely reported.…”
Section: Integration With Prior Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior limited work in health professions education suggests associations between achievement goals (measured with various instruments) and academic performance, self-efficacy, burnout and frustration. [29][30][31][62][63][64][65][66] However, validity evidence for achievement goals assessments in the health professions has been sparsely reported.…”
Section: Integration With Prior Workmentioning
confidence: 99%
“…the 2 × 2 framework). These instruments have been used widely in non‐health professions fields and occasionally in medical and pharmacy education . Modest validity evidence for AGQ‐R scores has accumulated in non‐health professions education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study not only investigated the satisfaction of students with online teaching during the epidemic, but also investigated the in uencing factors of psychological stress in college students' learning. The result showed that female college students were more likely to have psychological pressure on learning than male college students, the possible reason was that they have higher requirements for themselves and higher expectations for academic performance [12]. College students from rural areas were more prone to psychological stress in learning.…”
Section: Discussionmentioning
confidence: 96%
“…Empirical findings of educational research had proven that goal orientation determines students' cognitive and behavioral reactions as well as their educational performance (Barkur, Govindan, & Kamath, 2013;Hall, Hanna, Hanna, & Hall, 2015;Barzegar, 2012;Chen & wong, 2015).…”
Section: Discussionmentioning
confidence: 99%